The comparsion of effectiveness between grab start and track start in competitive swimming - Chen, S.-T.; Tang, W.-T. (ISB Congress, 2005)
The purpose of this study was to compare the grab start with the track start in kinematics (horizontal distance of entry) and kinetics variables (peak ground reaction force, peak vertical and horizontal force, speed strength index, i.e., SSI, impulse), and to integrate variables to estimate the starting efficiency (SSI-efficiency index, impulse-efficiency index ) for both starts. The results of this study should provide coach and swimmer with different perspectives on comparative advantages of start techniques.